La morada de los muertos. Cementerios extranjeros en México 1826-1917 - Servín Orduño, Gabriela (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
The work that the reader has at its disposal part of a series of questions that I have appeared like part of my doctoral thesis on cemeteries during the Mexican XIXth century; the approach that I have had with these spaces of the death. It is investigation that tries to recover the space of the cemetery seen from a cultural history, departing from the methodological proposal of Philippe Ariés and Michel Vovelle. For the concrete case of the investigation. I centred my attention on the cemeteries destined to lodge to the foreigners' colonies that came to Mexico in the XIXth century, especially of the Englishmen, French and Spanish. Of the first subject-matters that are tackled in the work, it recounts to a conceptual context, in him some pressures are done on concepts that were tackled along the work, continuing for a national context, I focused on the study especially of the secularization since it was vital to know how this process happened to understand the creation of the civil cemeteries in Mexico. Likewise the foreigners' arrival to Mexico is tackled in a general way during the mentioned century. The investigation put special interest to raise how the transition was the step of the cemetery to the cemetery as well as the interference of the hygienic speech, what allowed us to approach and know as it was the process of creation of the cemeteries that they lodged to the English colony, to the French and Spaniard.

El trabajo que el lector tiene a su disposición parte de una serie de preguntas que me he planteado como parte de mi tesis doctoral sobre cementerios durante el siglo XIX mexicano; el acercamiento que he tenido con estos espacios de la muerte. Es una investigación que pretende recuperar el espacio del cementerio visto a partir de una historia cultural, partiendo de la propuesta metodológica de Philippe Ariés y Michel Vovelle. Para el caso concreto de la investigación centré mi atención en los cementerios destinados para albergar a las colonias de extranjeros que llegaron a México en el siglo XIX, especialmente de los ingleses, franceses y españoles. De las primeras temáticas que se abordan en el trabajo, refiere a un contexto conceptual, en él se hacen algunas presiones sobre conceptos que fueron abordados a lo largo del trabajo, siguiendo por un contexto nacional, me enfoqué al estudio sobre todo de la secularización ya que era vital conocer cómo se dio este proceso para entender la creación de los cementerios civiles en México. Así mismo se aborda de manera general la llegada de extranjeros a México durante el siglo mencionado. La investigación puso especial interés por plantear como fue la transición el paso del camposanto al cementerio así como la injerencia del discurso higiénico, lo que nos permitió acercarnos y conocer como fue el proceso de creación de los cementerios que albergaron a la colonia inglesa, a la francesa y española.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-D-2016-0319; Cementerio; Discurso higiénico; Rituales funerarios; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2135